Transglutaminase 2: Development of therapeutic antibodies reveals four inhibitory epitopes and confirms extracellular function in fibrotic remodelling. (5th April 2022) - Maamra, Mabrouka; Benayad, Osama Mehdi; Matthews, David; Kettleborough, Catherine; Atkinson, John; Cain, Katharine; Bon, Helene; Brand, Helen; Parkinson, Michael; Watson, Philip F.; Johnson, Timothy S.
Abstract : Background and Purpose: Transglutaminase type 2 (TG2) catalyses formation of ε ‐( γ ‐glutamyl)‐lysine bonds between proteins, including those of the extracellular matrix (ECM). Elevated extracellular TG2 leads to accelerated ECM deposition and reduced clearance that underlies tissue scarring and fibrosis. Many transglutaminase inhibitors exist and allowed for proof‐of‐concept studies in disease models, but their lack of specificity for the TG2 isoform, and/or poor pharmacokinetic/pharmacodynamic properties have limited their clinical application. We sought to develop a high affinity TG2‐specific antibody against extracellular TG2 activity, with characteristics suitable for therapeutic development. Experimental Approach: Individual human TG2 domains were used to immunize mice and generate hybridomas. Supernatants were screened for inhibition of recombinant human TG2 activity, with TG2 specificity determined by ELISA. Key Results: Thirteen TG2‐specific, hybridoma supernatants inhibited human transamidation activity. Each hybridoma was cloned and the antibody mapped to an epitope in the TG2 core domain, using phage display panning of a TG2 fragment library. Four distinct inhibitory epitopes were determined. The most effective antibodies (AB1, DC1, and BB7) bound to amino acids 313–327 (catalytic core), with an IC50 of approximately 6–7 nM. The antibodies inhibit TG2 in human cells and block ECM accumulation in a primary human proximal tubular epithelial cell model of fibrosis. Only 7 antibodies inhibited rat TG2, all with higher IC50 values. Conclusions and Implications: We identified a preferred inhibitory epitope in human TG2, developed antibodies with required characteristics for clinical development, and established that targeted inhibition of extracellular TG2 transamidation activity is sufficient to modify fibrotic remodelling. Abstract : Transglutaminase 2 (TG2) catalyses the formation of protein crosslinks. Excess activity is associated with tissue scarring and organ fibrosis. Most available anti‐TG2 therapies are either unspecific or have poor pharmacokinetic/pharmacodynamic properties for systemic application. Here, we developed anti‐TG2 antibodies with the potential for clinical development as anti‐fibrotic therapeutics.